Museum management: Sociological aspects - A. S. Bigvava (RUDN journal of Sociology)
The article is a review of the book by three Czech museum experts - M.J. Půček, M. Plaček and F. Ochrana Museum Management: Opportunities and Threats for Successful Museums (Springer International Publishing; 2021. 176 p.). The authors consider museums as the most important institutions for preserving and transmitting information about the past, emphasizing their important social role confirmed by the huge number of museums (according to UNESCO data for 2020 - 95 thousand) and their visitors (annually from 10 thousand in the smallest museums to 10 million in the largest and most famous ones). The book will be useful and interesting for the sociologist, since it shows that the museum functions are not limited to aesthetic experience or educational impact. Museums provide essential information about the development of society and its subsystems in the form of “collections of the past”, i.e. museums help us to consider current problems and phenomena retrospectively - through exhibitions creatively organized, systematically selected and “adapted” to different perceptions. To perform such diverse functions, the museum should be perceived as a special organization that requires clear strategic management, especially of opportunities and risks, and the authors outline those management paths that can make a museum popular and successful.